Implication Of Provisions Article 58 Paragraph (2) Law Number 15 Of 2019 Concerning Amendments To Law Number 12 Of 2011 Concerning The Formation Of Laws And Regulations On The Mechanism Of Harmonizing, Unifying And Consolidating The Conception Of Draft Regional Regulations - Muhammad Ali Badary (Fakultas Hukum Universitas Lampung, 2020)
Article 58 paragraph (2) of Law Number 15 of 2019 concerning Amendments to Law Number 12 of 2011 concerning the Formation of Legislative Regulations changes the position of the central government in the process of harmonizing, unifying and consolidating the conception of draft regional regulations. The formulation of norms and laying of norms of Article 58 paragraph (2) of Law Number 15 of 2019 has resulted in normative legal consequences on the authority of regional apparatuses which have been coordinating harmonization, unification and consolidation of the conception of draft regional regulations proposed by regional heads and also resulting in the position of the central government to participate in harmonizing the draft regional regulations initiated by the Regional People's Representative Council. This study aims to identify the normative problems posed by Article 58 paragraph (2) of Law Number 15 of 2019, especially with regard to the mechanism of harmonization, unification and consolidation of the conception of draft regional regulations. This type of research is a type of normative research and the approach used in this study is a statute approach, a conceptual approach, and an analytical approach. The results of this study indicate that Article 58 paragraph (2) of Law Number 15 of 2019 raises normative problems in at least two things, namely the institutional relationship between vertical agencies in the regions and local governments which both have the authority to harmonize, unify and consolidate the conception of draft regional regulations. The types of draft regional regulations are harmonized by the ministry or agency that administers government affairs in the field of Formulation of Legislation. This problem arises because the formulation of norms and the placement of the norms of Article 58 paragraph (2) of Law Number 15 of 2019 are inaccurate so that there needs to be a revision of the formulation or laying of norms regulating the authority of ministries or institutions that carry out government affairs in the field of Regulatory Formation. Legislation in the harmonization, unification and strengthening of the conception of draft regional regulations.